Морфология гонад и некоторые особенности формирования половых клеток у самок американской белой бабочки (Hyphantria cunea) - Богач, А.В. (Вестник зоологии, 1976)
The structure of the reproductive system and certain peculiarities in formation of sex cells were studied at different stages of development of the dangerous quarantine pest Hyphantria cunea Drur y. Morphogenesis of the entire reproductive system in this species completes at the pupa stage. From the moment of the imago first flight the number of oocytes is strictly fixed and cannot increase. In each ovariole several eggs ripe simultaneously. The reproductive system of this species has essential species peculiarities which explain to a certain extent the high reproduction potential of this pest.